Could albumin level explain the higher mortality in hemodialysis patients with pulmonary hypertension? - Yoo, Hugo Hyung Bok [UNESP]; Martin, Luis Cuadrado [UNESP]; Kochi, Ana Claudia [UNESP]; Rodrigues-Telini, Lidiane Silva [UNESP]; Barretti, Pasqual [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Matsubara, Beatriz Bojikian [UNESP]; Zannati-Bazan, Silméia Garcia [UNESP]; Franco, Roberto Jorge da Silva [UNESP]; Queluz, Thais Helena Abrahão Thomaz [UNESP] (Springer Nature, 2012)
Background: The pathogenesis of pulmonary hypertension (PH) in hemodialysis is still unclear. The aim of thisstudy was to identify the risk factors associated with the presence of PH in chronic hemodialysis patients and toverify whether these factors might explain the highest mortality among them.Methods: We conducted a retrospective study of hemodialysis patients who started treatment from August 2001to October 2007 and were followed up until April 2011 in a Brazilian referral medical school. According to theresults of echocardiography examination, patients were allocated in two groups: those with PH and those withoutPH. Clinical parameters, site and type of vascular access, bioimpedance, and laboratorial findings were comparedbetween the groups and a logistic regression model was elaborated. Actuarial survival curves were constructed andhazard risk to death was evaluated by Cox regression analysis.Results: PH > 35 mmHg was found in 23 (30.6%) of the 75 patients studied. The groups differed in extracellularwater, ventricular thickness, left atrium diameter, and ventricular filling. In a univariate analysis, extracellular waterwas associated with PH (relative risk = 1.194; 95% CI of 1.006 1.416; p = 0.042); nevertheless, in a multiple model,only left atrium enlargement was independently associated with PH (relative risk =1.172; 95% CI of 1.010 1.359;p = 0.036). PH (hazard risk = 3.008; 95% CI of 1.285 7.043; p = 0.011) and age (hazard risk of 1.034 per year of age;95% CI of 1.000 7.068; p = 0.047) were significantly associated with mortality in a multiple Cox regression analysis.However, when albumin was taken in account the only statistically significant association was between albuminlevel and mortality (hazard risk = 0.342 per g/dL; 95% CI of 0.119 0.984; p = 0.047) while the presence of PH lost itsstatistical significance (p = 0.184). Mortality was higher in patients with PH (47.8% vs 25%) who also had astatistically worse survival after the sixth year of follow up.Conclusions: PH in hemodialysis patients is associated with parameters of volume overload that sheds light on itspathophysiology. Mortality is higher in hemodialysis patients with PH and the low albumin level can explain thisassociation.© 2012 Greenfield et al.; licensee BioMed Central Ltd.
Keywords: End-stage renal disease; Hemodialysis; Prognostic; Pulmonary hypertension; adult; aged; albumin blood level; correlation analysis; echocardiography; extracellular fluid; female; follow up; hazard assessment; heart left ventricle filling; heart size; heart ventricle hypertrophy; heart ventricle wall; hemodialysis patient; human; hypervolemia; logistic regression analysis; major clinical study; male; mortality; pathophysiology; prognosis; proportional hazards model; pulmonary hypertension; retrospective study; risk assessment; risk factor; survival rate; vascular access; Brazil; Comorbidity; Female; Humans; Hypertension, Pulmonary; Male; Middle Aged; Prevalence; Renal Dialysis; Renal Insufficiency, Chronic; Risk Assessment; Serum Albumin; Survival Analysis; Survival Rate